Implementasi Konsep Islam Nusantara dalam Membentuk Karakter Semangat Kebangsaan pada Mata Pelajaran IPS (Studi Kelas IV SDN Tamansari 4 Probolinggo) - Ludfi Arya Wardana, Dzikrullah (Tarbiyatuna Kajian Pendidikan Islam, 2017)
Weakening of the values in unity and totality is indicated by the existence of learners who irresponsibility each other in cleaning up the school environment, make friend with the only same children from the richclass, thinking themselves / do not want to work together, and there are feuds between schools so often Brawl among students. Methods researchers used the collection of observation data, interviews, anddocumentation. While data are analyzed with Miles and Huberman model that is data reduction, datapresentation, and conclusion. Technique examination of data validity with triangulation of source andtechnique. The results showed that the implementation of the concept of Islamic archipelago relatedmaterial Spirit Nation show teachers implant a knowledge and understanding of the concepts of divinity, theessence of Spirit Nation, the importance of understanding human rights in human life, introducing Democracy byelection of class leader, deviding group of learning freely, then teachers aligning the thinking andunderstanding of students, introducing the values contained in Bhinneka Tunggal Ika (Unity in Diversity),inculcating students' interest in reading Islamic and Spirit Nation materials, and students discussing in theclassroom to find solutions to every constraints that are being Faced.